Three-dimensional full-ceramic composite structure photovoltaic nano power generation device and preparation method thereof

By designing a water-volt nanopower device with a three-dimensional fully ceramic composite structure, using the structure of nanopore insulation and conductive ceramics, it is prepared through co-pressure forming technology, and the problems of low power generation performance and poor mechanical stability of existing water evaporation power generation devices are solved. , achieving higher mechanical stability and output performance, suitable for the future development of hydrovoltaic power generation.

CN119210203AInactive Publication Date: 2024-12-27DALIAN MARITIME UNIVERSITY
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411264355.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing water evaporation power generation devices have problems with low power generation performance and poor mechanical stability, especially the film configuration is prone to fall off after contact with water, and the mechanical stability and power generation performance are unstable.

Method used

A three-dimensional all-ceramic composite structure water volt nanoelectric power generation device is designed, using a structure that combines insulating ceramics with nanopores and conductive ceramics. It is prepared by co-pressure forming technology. Conductive ceramics are used for current collecting power, and insulating ceramics provide voltage. , and increase the current and voltage through series or parallel connection.

Benefits of technology

Improve the mechanical stability and output performance of power generation devices, ensure that the stability and current magnitude of the device when used in water are proportional to the voltage magnitude, and solve the problems of vulnerability and unstable power generation performance of traditional power generation devices, and future application prospects widely.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119210203A_ABST
    Figure CN119210203A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of water evaporation power generation, and particularly relates to a three-dimensional full-ceramic composite structure photovoltaic nano power generation device and a preparation method thereof. The device comprises insulating ceramic with nano-pores, one end of the insulating ceramic along the length direction is connected with conductive ceramic with nano-pores, or two ends of the insulating ceramic along the length direction are respectively connected with conductive ceramic with nano-pores; the insulating ceramic and the conductive ceramic are of an integrally formed structure; the insulating ceramic with the nanopores is used for providing voltage, and the conductive ceramic with the nanopores is used for collecting current and taking electricity. The hydrovolt nanometer power generation device is prepared through a co-pressing forming technology, the process is simple, the prepared power generation device is high in mechanical stability, the internal ceramic structure is stable, the stability of the output performance of the device is guaranteed, the future application prospect is wide, and the hydrovolt nanometer power generation device has great significance in accelerating the future development of the hydrovolt power generation field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of water evaporation power generation, and in particular to a three-dimensional all-ceramic composite structure hydrovoltaic nano-power generation device and a preparation method thereof. Background Art

[0002] Using clean and sustainable green energy to convert into electrical energy to replace traditional fossil energy has become a new strategy for mankind to deal with the global energy crisis and environmental warming in recent years. However, traditional new energy capture technologies such as wind power generation, solar power generation, tidal power generation, etc. still have problems such as low return on investment, great influence of geographical conditions and limited production capacity, which restrict their development and cannot meet the huge demand for energy in today's society. Water evaporation is ubiquitous in nature and is an infinite cycle. Therefore, it is of great significance to study the application of water evaporation energy conversion. In the future, with the continuous emergence of new materials and new technologies, the performance and efficiency of hydrovoltaic generators will be further improved. Therefore, it is of great significance to improve the performance of hydrovoltaic nanogenerators by designing new device structures, selecting suitable materials, and improving preparation processes in the field of hydrovoltaic power generation.

[0003] In order to induce power generation by water evaporation, the power generation device must be porous and hydrophilic, and the material system used is also constantly enriched, from the initial carbon nanoparticles to other porous materials or composite materials such as graphene materials, conductive polymers, nanostructured silicon and metal organic frameworks. However, most of its device configurations are thin-film (simply by coating or attaching to the skeleton material), and this configuration has limitations, such as thin-film devices are easy to fall off after contact with water, poor mechanical stability, and unstable power generation performance. Therefore, the design and construction of the device structure plays a vital role in improving the mechanical stability and output performance of the device. Summary of the invention

[0004] In view of the defects of current water evaporation power generation devices, the present invention provides a three-dimensional all-ceramic composite structure water evaporation nano power generation device and a preparation method thereof, which solves the problems of low power generation performance and poor mechanical stability of existing power generation devices.

[0005] In order to achieve the above object, the technical solution of the present invention is as follows:

[0006] On the one hand, the present invention provides a three-dimensional all-ceramic composite structure hydrovoltaic nano-power generation device, which includes an insulating ceramic with nanopores, one end of the insulating ceramic along the length direction is connected to a conductive ceramic with nanopores, or the two ends of the insulating ceramic along the length direction are respectively connected to conductive ceramics with nanopores; the insulating ceramic and the conductive ceramic are an integrally formed structure; the insulating ceramic with nanopores is used to provide voltage, and the conductive ceramic with nanopores is used to collect current and draw electricity.

[0007] In the above technical solution, further, the material of the conductive ceramic is antimony tin oxide, indium tin oxide, fluorine tin oxide, zinc oxide, copper oxide, and any one of silver, copper, gold, platinum, palladium and their alloys.

[0008] In the above technical solution, further, the material of the insulating ceramic is any one of aluminum oxide, silicon oxide, iron oxide, and titanium dioxide.

[0009] In the above technical solution, further, the pore diameter of the nanopore is 10-30nm.

[0010] In the above technical solution, further, the shape of the device is any one of a quadrangular prism, a cylindrical shape, and a sheet shape.

[0011] Another aspect of the present invention provides a method for preparing the above-mentioned three-dimensional all-ceramic composite structure hydrovoltaic nano-power generation device, the method comprising the following steps:

[0012] (1) placing nano-conductive ceramic material powder into a ball mill, mixing and grinding with a binder under the action of a grinding aid, and drying to obtain conductive ceramic powder;

[0013] (2) placing the nano insulating ceramic material powder into a ball mill, mixing and grinding with a binder under the action of a grinding aid, and drying to obtain insulating ceramic powder;

[0014] (3) placing the conductive ceramic powder and the insulating powder into the mold in different areas, with the conductive ceramic powder and the insulating ceramic powder in direct contact with each other, and pressing and molding using a co-pressing molding technology to obtain a green body;

[0015] (4) After the green body is sintered, a three-dimensional all-ceramic composite structure hydrovoltaic nano-power generation device is obtained.

[0016] In the above technical solution, further, in step (1) and step (2), the grinding aid includes ethanol or deionized water;

[0017] The adhesive includes PVB or PVA.

[0018] In the above technical solution, further, in step (3), the co-pressing pressure applied is 100-200 MPa.

[0019] In the above technical solution, further, in step (4), the sintering temperature is 800-1000° C. and the sintering time is 5-10 hours.

[0020] Method for using the above-mentioned hydrovoltaic nano-power generation device:

[0021] The conductive ceramic end of the hydrovoltaic nano-power generation device is immersed in water, and the conductive ceramic and the insulating ceramic lead wires to connect electrical appliances. The insulating ceramic provides voltage, and the voltage is proportional to the length of the insulating ceramic. The above-mentioned power generation devices can be connected in series or in parallel to obtain a larger current or voltage.

[0022] The beneficial effects of the present invention are:

[0023] The hydrovoltaic nanometer power generation device of the present invention increases the current collection and power supply area through three-dimensional nanoporous conductive ceramics, ensuring that the device can generate a large current. The insulating part ensures the voltage generated by the device. The effective pore surface area of ​​the conductive ceramic and the length of the insulating ceramic are proportional to the current and voltage respectively.

[0024] The hydrovoltaic nano-power generation device of the present invention is prepared by co-pressing molding technology, which has a simple process. The prepared power generation device has high mechanical stability and a stable internal ceramic structure, which ensures the stability of the device output performance and solves the problems that traditional power generation devices are easily damaged when exposed to water, have low mechanical stability, small current, and unstable power generation performance.

[0025] Increasing voltage, current and output power by connecting multiple devices in series or in parallel has broad application prospects in the future and is of great significance to accelerating the future development of the hydrovoltaic power generation field. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The schematic diagram of the structure of the hydrovoltaic nanometer power generation device of the present invention, a is a power generation device with conductive ceramics at one end, b is a power generation device with symmetrical conductive ceramics at both ends, and c is a power generation device with asymmetrical conductive ceramics at both ends;

[0027] Figure 2 This is a scanning electron microscope photo of the hydrovoltaic nano-power generation device of Example 1, a is the microstructure of the conductive ceramic, and b is the microstructure of the insulating ceramic;

[0028] Figure 3 The performance diagram of the hydrovoltaic nano-power generation device generator of Example 1, a is the voltage-time curve, b is the current-time curve, and c is the curve of the device's voltage, current and power density changing with load resistance. DETAILED DESCRIPTION

[0029] To further explain the present invention in detail. The following is a description of the purpose, technical solutions and advantages of the present invention in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0030] A three-dimensional all-ceramic composite structure hydrovoltaic nano-power generation device, comprising: an insulating ceramic with nanopores, one end of the insulating ceramic is connected to a conductive ceramic with nanopores ( Figure 1 a), or both ends of the insulating ceramic are connected to conductive ceramics with nanopores; the insulating ceramic and the conductive ceramic are an integrally formed structure.

[0031] One embodiment of the present invention is as follows Figure 1 As shown in b, the two ends of the insulating ceramic are respectively connected with symmetrical conductive ceramics with nanopores.

[0032] One embodiment of the present invention is as follows: Figure 1 As shown in c, the two ends of the insulating ceramic are respectively connected with asymmetric conductive ceramics with nanopores.

[0033] The present invention will be further described below with reference to the embodiments.

[0034] Example 1

[0035] A method for preparing a three-dimensional all-ceramic composite structure hydrovoltaic nano-power generation device comprises the following steps:

[0036] (1) mixing and grinding nano-tin antimony oxide powder, ethanol, and PVA in a mass ratio of 1:20:0.02 in a ball mill, and drying to obtain a conductive ceramic powder;

[0037] (2) putting nano-silicon dioxide powder, ethanol, and PVA in a mass ratio of 1:20:0.02 into a ball mill, mixing and grinding, and drying to obtain insulating ceramic powder;

[0038] (3) placing the conductive ceramic powder and the insulating ceramic powder into the mold in different areas, with the powder interfaces in direct contact, and using co-pressing technology to co-press at a pressure of 120 MPa to form a strip-shaped green body with tin antimony oxide at both ends and silicon dioxide in the middle, with a green body size of about 6 mm*2 mm*35 mm;

[0039] (4) After the strip green body was sintered at 900°C for 5 hours, a three-dimensional all-ceramic composite structure hydrovoltaic nano-power generation device was obtained, in which the length of antimony tin oxide at both ends was 6 mm and the length of silicon dioxide in the middle was 23 mm.

[0040] Figure 2 The electron microscope photos of the conductive ceramic and the insulating ceramic of Example 1 are shown in FIG. Figure 2 a is the microstructure of the conductive ceramic, which shows nanopores smaller than 20 nm and relatively large pores. Figure 2 b is the microstructure of insulating ceramics, which shows nanopores of 20 nm and larger pores. The nanopores are used to generate electricity through the hydrovoltaic effect, and the larger pores provide more channels for water, providing a water source for the nanopores in the device.

[0041] The antimony tin oxide at both ends of the three-dimensional all-ceramic composite structure hydrovoltaic nano-power generation device prepared in Example 1 was led out with wires for connecting electrical appliances, and was placed in a container filled with deionized water so that the antimony tin oxide at one end was inserted into the water and the rest was exposed to the water surface. The voltage of the power generation device was measured to be 0.68V and the short-circuit current was 1.25μA.

[0042] Example 2

[0043] A method for preparing a three-dimensional all-ceramic composite structure hydrovoltaic nano-power generation device comprises the following steps:

[0044] (1) mixing and grinding nano-tin antimony oxide powder, ethanol, and PVA in a mass ratio of 1:20:0.02 in a ball mill, and drying to obtain a conductive ceramic powder;

[0045] (2) putting nano-silicon dioxide powder, ethanol, and PVA in a mass ratio of 1:20:0.02 into a ball mill, mixing and grinding, and drying to obtain insulating ceramic powder;

[0046] (3) placing the conductive ceramic powder and the insulating ceramic powder into a mold in different areas, with the powder interfaces in direct contact, and using a co-pressing molding technology to co-press at a pressure of 120 MPa to form a strip-shaped green body with antimony tin oxide at one end and silicon dioxide at the other end, with a green body size of about 6 mm*2 mm*35 mm;

[0047] (4) After the strip green body was sintered at 900° C. for 5 hours, a three-dimensional all-ceramic composite structure hydrovoltaic nano-power generation device with a length of 6 mm for antimony tin oxide and a length of 27 mm for silicon dioxide was obtained.

[0048] Wires were led out from the antimony tin oxide end and the silicon dioxide end of the three-dimensional all-ceramic composite structure hydrovoltaic nano-power generation device prepared in Example 2 for connecting electrical appliances. The device was placed in a container filled with deionized water so that the antimony tin oxide was inserted into the water and the rest of the device was exposed above the water surface. The voltage of the power generation device was measured to be 0.94V and the short-circuit current was 1.03μA.

[0049] Example 3

[0050] A method for preparing a three-dimensional all-ceramic composite structure hydrovoltaic nano-power generation device comprises the following steps:

[0051] (1) mixing and grinding nano-indium tin oxide powder, ethanol, and PVA in a mass ratio of 1:20:0.02 in a ball mill, and drying to obtain a conductive ceramic powder;

[0052] (2) mixing and grinding nano-silicon oxide powder, ethanol, and PVA in a mass ratio of 1:20:0.02 in a ball mill, and drying to obtain insulating ceramic powder;

[0053] (3) placing the conductive ceramic powder and the insulating ceramic powder into a mold in different areas, with the powder interfaces in direct contact, and using a co-pressing molding technology to co-press at a pressure of 100 MPa to form a strip-shaped green body with indium tin oxide at one end and silicon dioxide at the other end, with a green body size of about 6 mm*2 mm*35 mm;

[0054] (4) After the strip green body was sintered at 950° C. for 5 hours, a three-dimensional all-ceramic composite structure hydrovoltaic nano-power generation device with an indium tin oxide length of 6.2 mm and a silicon dioxide length of 24 mm was obtained.

[0055] Wires were led out from the indium tin oxide end and the silicon dioxide end of the three-dimensional all-ceramic composite structure hydrovoltaic nano-power generation device prepared in Example 3 for connecting electrical appliances. The device was placed in a container filled with deionized water so that the indium tin oxide was inserted into the water and the rest of the device was exposed above the water surface. The voltage of the power generation device was measured to be 0.7V and the short-circuit current was 1.266μA.

[0056] Example 4

[0057] A method for preparing a three-dimensional all-ceramic composite structure hydrovoltaic nano-power generation device comprises the following steps:

[0058] (1) mixing and grinding nano-tin antimony oxide powder, alcohol, and PVA in a mass ratio of 1:20:0.02 in a ball mill, and drying to obtain a conductive ceramic powder;

[0059] (2) mixing and grinding nano-alumina powder, ethanol, and PVA in a mass ratio of 1:20:0.02 in a ball mill, and drying to obtain insulating ceramic powder;

[0060] (3) placing the conductive ceramic powder and the insulating ceramic powder into a mold in different areas, with the powder interfaces in direct contact, and using a co-pressing molding technology to co-press at a pressure of 200 MPa to form a strip-shaped green body with antimony tin oxide at one end and aluminum oxide at the other end, with a green body size of about 6 mm*2 mm*35 mm;

[0061] (4) After the strip green body was sintered at 1000° C. for 5 hours, a three-dimensional all-ceramic composite structure hydrovoltaic nano-power generation device with an antimony tin oxide length of 5.8 mm and an aluminum oxide ceramic length of 26 mm was obtained.

[0062] Wires were led out from the antimony tin oxide end and the aluminum oxide end of the three-dimensional all-ceramic composite structure hydrovoltaic nano-power generation device prepared in Example 4 for connecting electrical appliances. The device was placed in a container filled with deionized water so that the antimony tin oxide was inserted into the water and the rest of the device was exposed above the water surface. The voltage of the power generation device was measured to be 0.8V and the short-circuit current was 1.11μA.

[0063] The above embodiments are only preferred embodiments of the present invention and are not intended to limit the implementation methods. The protection scope of the present invention shall be subject to the scope defined in the claims. Other different forms of changes or modifications may be made based on the above description. Obvious changes or modifications derived therefrom are still within the protection scope of the present invention.

Claims

1. A three-dimensional all-ceramic composite structure hydrovoltaic nano-power generation device, characterized in that: The device includes an insulating ceramic with nanopores, one end of the insulating ceramic along the length direction is connected to a conductive ceramic with nanopores, or both ends of the insulating ceramic along the length direction are respectively connected to conductive ceramics with nanopores; the insulating ceramic and the conductive ceramic are an integrally formed structure; the insulating ceramic with nanopores is used to provide voltage, and the conductive ceramic with nanopores is used to collect current and draw electricity.

2. The three-dimensional all-ceramic composite structure hydrovoltaic nano-power generation device according to claim 1, characterized in that: The conductive ceramic is made of any one of antimony tin oxide, indium tin oxide, fluorine tin oxide, zinc oxide, copper oxide, silver, copper, gold, platinum, palladium and alloys thereof.

3. The three-dimensional all-ceramic composite structure hydrovoltaic nano-power generation device according to claim 1, characterized in that: The insulating ceramic is made of any one of aluminum oxide, silicon oxide, iron oxide and titanium dioxide.

4. The three-dimensional all-ceramic composite structure hydrovoltaic nano-power generation device according to claim 1, characterized in that: The pore diameter of the nanopore is 10-30 nm.

5. The three-dimensional all-ceramic composite structure hydrovoltaic nano-power generation device according to claim 1, characterized in that: The device is in any shape of a quadrangular prism, a cylinder or a sheet.

6. A method for preparing the three-dimensional all-ceramic composite structure hydrovoltaic nano-power generation device according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: (1) placing nano-conductive ceramic material powder into a ball mill, mixing and grinding with a binder under the action of a grinding aid, and drying to obtain conductive ceramic powder; (2) placing the nano insulating ceramic material powder into a ball mill, mixing and grinding with a binder under the action of a grinding aid, and drying to obtain insulating ceramic powder; (3) placing the conductive ceramic powder and the insulating ceramic powder into a mold in different areas, with the conductive ceramic powder and the insulating ceramic powder in direct contact with each other, and pressing and molding using a co-pressing molding technology to obtain a green body; (4) After the green body is sintered, a three-dimensional all-ceramic composite structure hydrovoltaic nano-power generation device is obtained.

7. The preparation method according to claim 6, characterized in that: In step (1) and step (2), the grinding aid comprises ethanol or deionized water; The adhesive includes PVB or PVA.

8. The preparation method according to claim 6, characterized in that: In step (3), the co-pressing pressure is 100-200 MPa.

9. The preparation method according to claim 6, characterized in that: In step (4), the sintering temperature is 800-1000° C. and the sintering time is 5-10 hours.

Citation Information

Patent Citations

  • Low resistance transparent conductive film and preparation method

    CN105225728A

  • Janus water photovoltaic power generation material as well as preparation method and application thereof

    CN114212780A

  • Preparation method of functional area of photo-thermoelectric conversion device based on HV-PN junction

    CN115037188A

  • Flexible wet-based power generation device based on nano oxide particles and preparation method of flexible wet-based power generation device

    CN117526762A

  • Electrolyte separator and method of making the electrolyte separator

    US20110236743A1